Distal extension mandibular removable partial denture with implant support - Bural, Canan (Eur J Dent, 2016)
This case report describes the fabrication of a distal extension removable partial denture (RPD) of a 65-year-old man with implant support. Loss of fibroelasticity of the peripheral tissues and reduced mandibular vestibular sulcular depth due to a previous surgical resection and radiotherapy at the right side were the main clinical factors that created difficulty for denture retention and stability. The fabrication of a mandibular RPD supported by anterior teeth and two bilaterally placed implants in the molar area to convert from Kennedy Class 1 design to Kennedy Class 3 implant-bounded RPD is reported. Retention and stability of the denture were improved with implant support on the distal extension site of the RPD. The common clinical problems about distally extended RPDs are lack of retention and stability due to the movement around the rotational axis. Dental implant placement to the distal edentulous site minimizes the potential dislodgement of the RPD is popular. Implant-supported RPD can be suggested as an advantageous and cost-effective treatment option for the partially edentulous patients.